Design and field methods of the ARISE network COVID-19 rapid monitoring survey - Hemler, Elena C.; Korte, Michelle L.; Lankoande, Bruno; Millogo, Ourohiré; Assefa, Nega; Chukwu, Angela; Workneh, Firehiwot; Tinkasimile, Amani; Lyatuu, Isaac; Soura, Abdramane; Wang, Dongqing; Madzorera, Isabel; et al. (The American journal of tropical medicine and hygiene, 2021)
ABSTRACT. The coronavirus disease 2019 (COVID-19) pandemic has significant health and economic ramifications across sub-Saharan Africa (SSA). Data regarding its far-reaching impacts are severely lacking, thereby hindering the development of evidence-based strategies to mitigate its direct and indirect health consequences. To address this need, the Africa Research, Implementation Science, and Education (ARISE) Network established a mobile survey platform in SSA to generate longitudinal data regarding knowledge, attitudes, and practices (KAP) related to COVID-19 prevention and management and to evaluate the impact of COVID-19 on health and socioeconomic domains. We conducted a baseline survey of 900 healthcare workers, 1,795 adolescents 10 to 19 years of age, and 1,797 adults 20 years or older at six urban and rural sites in Burkina Faso, Ethiopia, and Nigeria. Households were selected using sampling frames of existing Health and Demographic Surveillance Systems or national surveys when possible. Healthcare providers in urban areas were sampled using lists from professional associations. Data were collected through computer-assisted telephone interviews from July to November 2020. Consenting participants responded to surveys assessing KAP and the impact of the pandemic on nutrition, food security, healthcare access and utilization, lifestyle, and mental health. We found that mobile telephone surveys can be a rapid and reliable strategy for data collection during emergencies, but challenges exist with response rates. Maintaining accurate databases of telephone numbers and conducting brief baseline in-person visits can improve response rates. The challenges and lessons learned from this effort can inform future survey efforts during COVID-19 and other emergencies, as well as remote data collection in SSA in general.